Program Arcade Games With Python and Pygame - Craven, Paul (Apress : Imprint: Apress, 2016)
This fine book shows you how to build fun, cool arcade games using the Python programming language and the PyGame framework, a Python-based game application development engine. Use Python and Pygame to learn and build arcade games! What You'll Learn How to create quiz games How to start using graphics How to create and animate graphics How to integrate and use game controllers How to add sound and bitmapped graphics How to build grid-based games.